Educating Mars. Educational Innovation Profitability and Professional Versatility - Herrero Fernández-Quesada, Mª Dolores (Cuadernos de Historia Moderna, 2016)
This paper is focused on one of the successes on military reformism, the new model of military, scientific and technical education of the Facultative Armies. The education of the military officer in the XVIII century will be the starting point in an attempt to approach to the profitability of the new education policy and military schools of engineers and artillery, the latter paradigm of military educational innovation. And from the academic world of this institution, we track the profitability of Mars’ education and among its most notable returns, professional versatility of officers who unwrapped in areas such as industrial espionage in Europe is analyzed, working together artillerymen and engineer Betancourt ; or who naturally transited from science to the new political economy, as Captain Vicente Alcalá Galiano did.